The novel allele, HLA-B*08:113, identified in a German cord blood donor and his mother - Strobel, Joachim; Ringwald, J.; Hauck-Dlimi, B.; Eckstein, Reinhold; Zingsem, Jürgen (Tissue Antigens, 2014)
The novel allele HLA-B*08:113 identified in two related individuals of Caucasian origin is described.
EVALuna2:15979